THE USE OF CUE CARDS IN TEACHING SPOKEN DECRIPTIVE TEXT(A CLASSROOM ACTION RESEARCH ON SEVENTH GRADE STUDENTS IN SMP 15 BANDUNG) - Lilis Suryani, - (2010)
The research reports on the use of cue cards in teaching spoken descriptive text. Based on some observation, the students` speaking scores were still low. Cue cards were applied in the research to improve the students` speaking scores. The aims of the research were to improve the progress of the students in producing spoken descriptive text in every cycle after using cue cards and to find out the advantages and disadvantages of the use of cue cards in teaching spoken descriptive text. The research used classroom action research and it was conducted for several weeks which covered two cycles. Every cycle consists of planning, acting, observing, and reflecting. The subjects were seventh grade students in SMP 15 Bandung. In collecting the data, existing document, observation sheet, test, and interview were employed. The result of the research showed that there was improvement of the students in producing spoken descriptive text in every cycle after using cue cards. The mean of the students` speaking test in cycle 1 was 68.6, with 31 students (70%) getting the scores above KKM. The mean of the students` speaking test in cycle 2 increased to 72.1, with 37 students (84%) getting the scores above KKM. In addition, the result of interview and observation sheet showed that cue card can be one of alternative media in teaching spoken descriptive text and it could encourage the students` motivation in learning descriptive text. Besides, the limitation of time was the disadvantages of using cue cards. For teachers who are interested in using cue cards, it is suggested carefully to select the appropriate pictures in using cue cards and to manage the length of time in given the lesson. Further researchers in the same field of research are suggested to use cue cards in different kinds of genre text.